Development of a Mathematics Dictionary as a Learning Media for Students in Elementary, Middle School and High School - Rosmaini, Rosmaini; Putri, Icha Elisyah; Sembiring, Putri Yolanda Br; Siringoringo, Rachel A; Siringoringo, Rona Maruli (Lembaga Riset Mutiara Akbar, 2024)
This research aims to develop learning media under the title